Disulfiram inhibits bacterial growth by inducing zinc-dependent reactive oxygen species - Luo, Qinyu; Wu, Zehua; Pan, Yihang; Zhang, Yan (Frontiers in Microbiology, 2025)
IntroductionThe discovery of novel antimicrobial mechanisms among existing clinical drugs is urgently needed. Disulfiram, an FDA-approved treatment for alcohol dependence, exhibits broad-spectrum antibacterial effects. However, its mechanism of action remains incompletely understood.MethodsThe antimicrobial activity of disulfiram was assessed using bacterial growth curves and colony-forming unit assays. Cytotoxicity was evaluated via propidium iodide staining and flow cytometry. Synergy with polymyxins or kanamycin was examined using checkerboard assays. RNA-seq was performed on disulfiram-treated E. coli, and differentially expressed genes were analyzed using the R package limma. Intracellular reactive oxygen species (ROS) levels were measured with fluorescent probes and flow cytometry.ResultsDisulfiram exhibited bacteriostatic, but not bactericidal, effects against E. coli and S. aureus. However, it significantly enhanced the bactericidal activity of colistin or kanamycin, both in vitro and in a murine E. coli infection model. Transcriptomic analysis revealed oxidative stress and zinc-related responses in disulfiram-treated E. coli. The bacteriostatic effects were reversed by the ROS scavenger N-acetyl-l-cysteine and zinc chelators, whereas zinc supplementation enhanced ROS production and growth inhibition.DiscussionThis study identifies a zinc-dependent ROS-mediated mechanism underlying the bacteriostatic activity of disulfiram. Although the in vivo concentrations of disulfiram during standard therapy are below its MIC, its synergistic effect with colistin suggests clinical relevance as an adjuvant. Disulfiram-induced redox stress and zinc modulation likely compromise bacterial antioxidant defenses and membrane integrity. These findings support further investigation of dithiocarbamate-based compounds as potential adjuvants or scaffolds for novel antimicrobial development.